Carbon Footprint of Household Food Waste - del Rio, Joana Marie Pabulayan; Gonzales, Arlene Cerna Urgena (Asian Journal of Multidisciplinary Studies, 2019)
Household food waste is a major contributor of pollution. Translated into greenhouse gas production through the amount of carbon footprint, it is said that the environment could only take as much but not more. Taken from the individual family households in small quantities, it may not seem to make a difference but in global perspective, the amount of food waste produced per year could feed millions of hungry people around the world. The negative marks of the issue are not only in terms of environmental and health safety but also in socio-economic sustainability. In the international scene, numerous accounts of studies cite that food wastage is directly influenced by the monthly income earned by a family. Other studies contradict such statement while others assess that no relationship could be found to exist between the amount of household food waste and family income. In this study, fifteen families from three different locales participated to undertake this research in anticipation of finding the carbon footprint generated through household food waste from the low to middle income family groups in five days. Results show that the average percentage of food waste produced was directly related to the income yield per month. Furthermore, it was found out that the higher the family income, the higher the household food waste as well as the generated carbon footprint. With these results, it was suggested that a closer monitoring of household food waste generated be done to identify other problematic effects because awareness and prevention is still the best mitigating effort that people could give in order to achieve great and lasting results.